The role of molecular pathology in the precision diagnosis and subclassification of hepatocellular carcinoma - Kathryn Effendi; Wit Thun Kwa; Akihisa Ueno; Michiie Sakamoto (Faculty of Medicine, Universitas Trisakti, 2022)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer death worldwide despite recent advances in surveillance and therapeutic management. The outcomes for HCC patients remain poor, often as a result of late diagnosis or lack of effective treatments. Early detection and precise diagnosis are evidently crucial in improving the prognosis of HCC. However, HCC is a highly heterogeneous cancer with various clinical backgrounds and altered molecular pathways; these factors make its precise diagnosis more difficult. Approximately 25% of HCCs harbor actionable mutations, which are yet to be translated into clinical practice. In the era of precision medicine, molecular or genomic information are indispensable for HCC diagnosis and prognosis. Exploring genomic alterations has become a requirement for identifying the molecular subtypes of HCC. Recent studies have introduced molecular markers to help identify early HCC and to clarify its multistep process of carcinogenesis. The subclassification of tumors into proliferation class and nonproliferation class HCCs gives pointers to the HCC phenotype and facilitates the selection of appropriate treatments. In this review, we broadly summarize some of the latest insights into HCC subclassification from the perspective of molecular pathology. Immunohistochemistry-based subclassification allows improved characterization of HCC in daily clinical practice. Moreover, analysis of the immune microenvironment, intra-tumoral morphological heterogeneity, and imaging features gives additional information regarding the classification of HCC. Combinations of these approaches are expected to inform and advance the precision diagnosis and management of HCC.